2012
DOI: 10.1103/physrevb.86.081408
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing the ground state in zigzag-edged graphene nanoribbons by dihydrogenation

Abstract: The dihydrogenation effects in the zigzag-edged graphene nanoribbons (ZGNRs) have been systematically investigated by first-principles calculations. Due to the dihydrogenation, the edges effectively turn to the so-called Klein edges, which results in localized edge states in (0, 2 3 π) and extended bulk states in (2 3 π,π). Compared with monohydrogenation, the edge magnetic moment is substantially increased and the edge states get much more delocalized, which results in the most attractive observation that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
(54 reference statements)
2
34
0
Order By: Relevance
“…If one simply changes the ribbon to FM states, it will be found that the FM state is not energetic preferable because an additional exchange energy in ribbon unit cell is introduced. 34 It is also a natural choice of the paramagnetic (PM) ground state for ASiNR, because the edge atoms always show alternative spin states in either, sp 2 -σ or pz-π subspace, as shown in Fig. 1(e).…”
Section: A General Modelmentioning
confidence: 99%
“…If one simply changes the ribbon to FM states, it will be found that the FM state is not energetic preferable because an additional exchange energy in ribbon unit cell is introduced. 34 It is also a natural choice of the paramagnetic (PM) ground state for ASiNR, because the edge atoms always show alternative spin states in either, sp 2 -σ or pz-π subspace, as shown in Fig. 1(e).…”
Section: A General Modelmentioning
confidence: 99%
“…The edge states formed at the bearded edges are more delocalized than those at the zigzag edges, decaying more slowly into the middle of the nanoribbon [8]. Due to the large magnetic moment and the slow decay, the exchange energy gain stabilizing the antiferromagnetic state in the dihydrogen-terminated ZGNRs is an order of magnitude larger than that in the monohydrogenterminated ZGNRs [8].…”
Section: Introductionmentioning
confidence: 93%
“…Since the magnetic moment decays exponentially from the edge to the middle of the ZGNR with a finite decay length, the exchange interaction between the opposite edges decreases with increasing nanoribbon width due to the decrease of the magnetic moment at the middle of the ZGNR. In the dihydrogen-terminated ZGNRs, which are equivalent to the bearded (Klein) edge graphene nanoribbons, the magnetic moment at the bearded edges is much larger than that at the zigzag edges of the monohydrogen-terminated ZGNRs [8]. The edge states formed at the bearded edges are more delocalized than those at the zigzag edges, decaying more slowly into the middle of the nanoribbon [8].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations